In Vitro Analysis of the Sealing Ability of Different Root Canal Sealers Under Thermomechanical Stress - Anne P. George; Nevil Mathews; Mustafa Hussein Alattas; Krishnan Hari; Ayman Moaz Abulhamael; Tisson Varghese Job (Journal of Pharmacy and Bioallied Sciences)
Background: The ability of a root canal sealer to fill spaces and prevent microleakage is a major factor in the quality of root canal therapy. The efficacy of root canal sealers to seal may be impacted by thermomechanical stress, which mimics clinical chewing forces and temperature variations. Materials and Methods: Forty extracted human single-rooted teeth that had been removed were split into four groups at random (n = 10). Group 1 was obturated using epoxy resin, Group 2 was obturated using calcium silicate, Group 3 was obturated using bioceramic, and Group 4 was obturated using zinc oxide eugenol. 10,000 thermocycles (5°C to 55°C) and 100,000 mechanical loading cycles at 50 N were used to apply thermomechanical stress to the specimens. Following this, the teeth were submerged in 1% methylene blue dye for 24 hours. Under a stereomicroscope, dye penetration was assessed in millimeters after sectioning. Results: With a mean value of 0.6 ± 0.1 mm, Group 1 (Epoxy resin) showed the least amount of dye penetration, followed by Group 3 (Bioceramic) with 0.9 ± 0.2 mm. Group 4 (zinc oxide eugenol) had the largest dye penetration (1.8 ± 0.4 mm), while Group 2 (calcium silicate) had moderate leakage (1.2 ± 0.3 mm). Group 1 performed substantially better than Group 4, according to statistical analysis using ANOVA, which showed significant differences between the groups (P < 0.05). Conclusion: Superior sealing performance under thermomechanical stress conditions was established by epoxy resin-based sealers, indicating their possible use in clinical situations. Sealers based on zinc oxide eugenol, showed the most leakage, indicating the need for more formulation improvements.